The use of Oil Palm Mesocarp Serat as a Substitute for Synthetic Serat in the Manufacture of Fiberglass Composites - Prasanto Bimantio, Mohammad; Marturia Sembiring, Haris; Astuti Widyowanti, Reni (Jurnal Penelitian Kelapa Sawit, 2023)
One of the biggest wastes produced by palm oil mills and their limited use of fuel is palm serat. This waste can be used as a fiberglass composite material. The purpose of this study is to analyze the influence of variations in palm serat and catalysts (mepoxe) on the quality of composites, and analyze the compositions that can produce the best product quality. This study used a complete block design (RBL) with 2 factors. The first factor is the use of catalysts including A1:0.5%, A2:0.75%, and A3:1% and the second factor is the addition of palm serat including B1:7.5%, B2:10%, and B3:12.5 %. The best results were found in the composition of 1% catalyst and 10% palm serat (A3B2 sample) with a thickness of 4.61 mm, a waterproof value of 0.0019 gram, a porosity value of 2.51% which met SNI No.03-1027-1995 and a maximum bending test (fM) of 7.07 MPa / mm and a bending break (fB) of 6.62 MPa / mm so that the sample had better flexibility among other samples but, compared to the control sample, are still relatively weak. The best results for the strongest sample were obtained at the composition of 1% catalyst and 10% palm serat (A3B3 sample) with a thickness of 5.37 mm, a waterproof value of 0.0027 grams, a porosity value of 2.79%, and a load strength of 208.7929 N.